2022
DOI: 10.3390/healthcare10060995
|View full text |Cite
|
Sign up to set email alerts
|

Adult Inpatients’ Perceptions of Their Fall Risk: A Scoping Review

Abstract: Patient falls in hospitals continue to be a global concern due to the poor health outcomes and costs that can occur. A large number of falls in hospitals are unwitnessed and mostly occur due to patient behaviours and not seeking assistance. Understanding these patient behaviours may help to direct fall prevention strategies, with evidence suggesting the need to integrate patients’ perspectives into fall management. The aim of this scoping review was to explore the extent of the literature about patients’ perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 70 publications
0
30
0
4
Order By: Relevance
“…Further, Swedish research has found that older people see falling as an inevitable fact of existence but believe that there is ‘ more to life than risk avoidance ’ (Gustavsson et al, 2018). Furthermore, healthcare professionals have observed differences between individuals' perceptions of their risk of falling and their own assessments (Dabkowski et al, 2022). The implications that follow are that risk–based messaging for falls prevention may not be the ideal way to communicate necessary information, given that people are unlikely to identify themselves as at risk and differ in their goals for maintaining their wellbeing.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Further, Swedish research has found that older people see falling as an inevitable fact of existence but believe that there is ‘ more to life than risk avoidance ’ (Gustavsson et al, 2018). Furthermore, healthcare professionals have observed differences between individuals' perceptions of their risk of falling and their own assessments (Dabkowski et al, 2022). The implications that follow are that risk–based messaging for falls prevention may not be the ideal way to communicate necessary information, given that people are unlikely to identify themselves as at risk and differ in their goals for maintaining their wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Engaging in meaningful conversations with older people to identify what they want is therefore necessary. Feelings of disempowerment, loss of control and threats to self‐identity frequently accompany a hospitalisation, and personal considerations of independence and dignity may influence a patient's desire to do what is medically advised (Dabkowski et al, 2022). Research examining the perspectives of older people on what dignity means in acute care centre on the themes of autonomy (involvement in decisions), safety and respect (Kerr et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations